Neurodiversity and Human Resource Development: A Systematic Literature Review - Afsar, Simran (Auckland University of Technology, 2025)
This Systematic Literature Review (SLR) examines the significance of implementing tailored neurodiverse training programmes to support individuals with neurodiversity. The review explores how Humanistic Learning Theory (HLT) and Digital Transformation (DT) can aid neurodiverse individuals by reducing cognitive load and minimising biases within teams. It further investigates how Human Resource Development (HRD) initiatives can be designed to assess and enhance the well-being of neurodiverse individuals. Following the PRISMA protocol, a standardised and transparent review process was conducted, encompassing a search across four databases: EBSCO, Google Scholar, ProQuest, and NZ Research. The inclusion and exclusion criteria were strictly developed based on thematic analysis, timeframe, language, article quality, and methodology. Initially, 440 articles were gathered across four databases, out of which 16 relevant peer-reviewed studies and 12 grey literature sources from global organisations were identified. The findings highlight the importance of incorporating HRD initiatives that promote neurodiverse well-being and how integrating a humanistic approach with DT can create effective, personalised training programmes. These approaches help reduce stigma and provide organisations with search strategies to foster inclusivity. This review contributes to existing literature by identifying gaps and proposing directions for future research. Additionally, it offers practical recommendations for organisations to implement neurodiversity-focused programmes that improve workplace inclusivity and well-being. This study emphasises the critical role of individualised support and inclusive practices in creating equitable opportunities for neurodiverse individuals.